John Wooden and John Calipari: excellence as a coach in different moments - Fabio Cassiano Neto; Alexandre Vinicius Bobato Tozetto; Benjamín Longarela Pérez; Larissa Galatti (Federación Extremeña de Balonmano; University of Extremadura, 2018)
Basketball has been studied a lot over the years and researches about coaches and coaching are also more frequently now. In National Collegiate Athletic Association (NCAA) basketball, John Wooden, former head coach of the University of California, Los Angeles (UCLA), is considered the greatest coach of all time after countless achievements and ten NCAA titles, being seven in a row and four undefeated. Nowadays, John Calipari, head coach of the University of Kentucky, is in the spotlight as one of the best coaches in the league, winning the National Championship in 2012 and achieving the best start of the season in Division I history during season 2014-2015 with 38 consecutive wins. Through documental analysis about the above mentioned coaches, scientific researches of coach and coaching concepts will be the basis to relate Wooden and Calipari to literature. The objective of the study is to recognize and classify the coaches knowledges following Côté and Gilbert (2009) proposal, in professional knowledge, interpersonal knowledge and intrapersonal knowledge.